JJCO Best Reviewer Award (Japanese Journal of Clinical Oncology, 2020)
Letermovir is used for cytomegalovirus prophylaxis after allogeneic hematopoietic cell transplantation (HCT) and reportedly increases tacrolimus exposure. Isavuconazole, a mold-active triazole antifungal, also inhibits cytochrome P450 3A and may affect tacrolimus pharmacokinetics. This retrospective study evaluated tacrolimus concentration-to-dose (C/D) ratios pre- and post-conversion from continuous intravenous infusion to oral administration in allogeneic HCT recipients receiving isavuconazole. Forty-five patients were stratified according to letermovir coadministration into the isavuconazole-alone group (ISCZ-alone; n = 9) and the isavuconazole with letermovir group (ISCZ + LMV; n = 36). The median C/Dciv ratios were 17.00 and 16.40 (ng/ml)/(mg/day), respectively (P = 0.81); the median C/Dpo ratios were 3.25 and 2.60 (ng/ml)/(mg/day), respectively (P = 0.77); and the median (C/Dpo)/(C/Dciv) ratios were 0.154 and 0.173, respectively (P = 0.72). Sensitivity analyses yielded consistent findings. Letermovir coadministration was not associated with significant differences in tacrolimus C/D ratios pre- or post-conversion to oral administration in allogeneic HCT recipients receiving isavuconazole.